2016
DOI: 10.1159/000446953
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Bowel Preparation for Laparotomy Gynecologic Surgery: A Prospective, Surgeon-Blinded Randomized Study

Abstract: Objective: To compare the surgeon's satisfaction during gynecological laparotomy surgery and patient's satisfaction as well as quality of life (QOL) among 3 groups of bowel preparations: no enema vs. sodium chloride enema vs. soap-suds enema (SSE). Materials and Method: Three hundred and thirty three women undergoing gynecological laparotomy surgery and without risks to bowel lumen entry between November 2014 and October 2015 were randomized to receive no enema (n = 111), sodium chloride enema (n = 111) or SSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…In another study, 333 women who had gynecological procedures were included. Overall surgeon satisfaction, operating perspective, and bowel packing efficacy were not significantly different between the two bowel preparation methods in this study (15) .…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…In another study, 333 women who had gynecological procedures were included. Overall surgeon satisfaction, operating perspective, and bowel packing efficacy were not significantly different between the two bowel preparation methods in this study (15) .…”
Section: Discussioncontrasting
confidence: 49%
“…Suadee and Suprasert (15) conducted a study on patients underwent gynecologic surgery and compared no bowel preparation with MBP. The study found no significant differences among each group regarding the return to bowel function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to identify only 1 RCT that studied the use of preoperative enemas during gynecologic laparotomy surgery. 12 Perioperative complications, surgical field visualization, efficacy of bowel packing, and surgeon and patient satisfaction were compared following no preoperative enema vs sodium chloride enema vs soap-suds enema. Of note, patients who were expected to have extensive surgery or entry in the bowel lumen were excluded.…”
Section: Level Of Evidence: Lowmentioning
confidence: 99%